Effect of Horticultural Land uses on Soil Properties and Organic Carbon Distribution in a Reclaimed Sodic Soil - S.K. Chaudhari; D.K. Sharma, Ashim Datta, Nirmalendu Basak (Journal of the Indian Society of Soil Science, 2015)
Information on soil properties and organic carbon distribution in reclaimed sodic soils under different horticultural fruit trees as well as how organic carbon stock varies depth-wise under these land uses is very limited. Therefore, four horticultural land uses namely, guava (Psidium guajava), litchi (Litchi chinensis), mango (Mangifera indica), and jamun (Syzygium cumini) were selected to study their effect on soil properties and distribution of soil organic carbon (SOC) onto different pools of their oxidizability in a reclaimed sodic soil. Soil samples were collected up to a depth of 60 cm i.e. 0-20, 20-40 and 40-60 cm from the above land uses. Results showed that soil pHw (soil: water ratio: 1:2) and bulk density (BD) increased with depth in all the land uses. Minimum and maximum pHw was associated with litchi (6.81) at 0-20 cm and jamun (7.73) at 40-60 cm depth of soil, respectively. Guava recorded minimum BD (1.45 Mg m-3) at 0-20 cm soil depth whereas, a maximum BD of 1.66 Mg m-3 was associated with litchi plantation at lower soil depths. Among the land uses, highest clay content (19.2%) at 0-20 cm was observed under litchi plantation followed by mango (17.3%), jamun (14.4%) and guava (13.9%). Litchi (1.49%) and mango (1.4%) recorded highest CaCO3 content at 0-20 cm soil depth. The amount of oxidizable organic C (OC) varied among the land uses, on an average, its amount was highest with guava (25.9 Mg C ha-1) followed by jamun (25.1 Mg C ha-1) = litchi (25.0 Mg C ha-1) > mango (16.5 Mg C ha-1) in surface soil. Total organic carbon (TOC) stock at surface soil in descending order was guava (28.8 Mg C ha-1) > jamun (27.3 Mg C ha-1) > litchi (25.7 Mg C ha-1) > mango (19.2 Mg C ha-1). In all the land uses, with depth increment passive pool carbon content was increased due to more physical, chemical and biochemical stabilization of organic carbon in lower depths of soil. Soils under guava plantation recorded highest SOC storage (61.0 Mg C ha-1) as well as maximum passive pool C (25.3 Mg C ha-1) up to 60 cm soil depth. Therefore, guava plants can be recommended in reclaimed sodic soils or otherwise barren degraded salt affected land for income generation to the farmers as well as environmental benefit to the mankind.